TRANSFORMING MEDICAL RECORDS INTO ACTIONABLE INSIGHTS THROUGH DATA VISUALIZATION DASHBOARDS - Nisak, Umi Khoirun; Ilmi, Laili Rahmatul; Natasya , Nabila Insyira; Kinanthi, Citra Anggun; Cholifah, Cholifah (Antis-publisher, 2025)
Objective: This community service aimed to educate healthcare workers at Aisyiyah Pandaan Inpatient Clinic on the process of medical record data, fostering data-driven decision-making in patient care. Method: In October 2024, a training program was conducted for 20 healthcare workers, focusing on medical record data analysis, interpretation, and presentation. Participants were trained on how to utilize medical data to support clinical decisions. Results: The training program led to a significant improvement in the participants' knowledge and abilities in medical record data analysis. The results were statistically significant with p-values: p < .001, p < .001, p = 0.003, p < .001, and p = 0.002. Novelty: This activity represents a novel initiative in empowering healthcare workers by enhancing their competencies in using medical record data for clinical decision-making, promoting efficiency and accuracy in patient care.